Cloud Follow-Up in Patients With Cardiovascular Implantable Electronic Devices: A Single-Region Study in China - Tong, Lin; Xiong, Shiqiang; Hou, Jun; Li, Jin; Qin, Shujuan; Zhang, Yangchun; Yang, Siqi; Qi, Lingyao; Chen, Xu; Luo, Yan; Zhang, Zhen; Deng, Haoyu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Due to seriously imbalanced distribution of follow-up clinics in China, routine in-office visits are erratically attended by many cardiovascular implantable electronic device (CIED) patients. Meanwhile, remote monitoring is significantly underutilized. Novel tools to address the current predicament of routine in-office visits in China is urgently needed. Objectives To assess the reliability and feasibility of cloud follow-up in CIED patients. Methods A total of 325 CIED patients from 13 hospitals in Sichuan Province, China, were enrolled. Information on patients’ sociodemographic and basic clinical characteristics was collected. All devices were tested and programmed with 5G-cloud follow-up platform in a real-time manner. All patients were surveyed about their acceptance of and preferences regarding cloud follow-up compared to routine in-office visits. Results Compliance with routine in-office visits in this region was 60.6%. None of the patients were enrolled in remote monitoring services. Clinically important predictors of non-compliance were elderly age (≥75 years old), odds ratio (OR) 2.392 (95% confidence interval, 1.111–5.150); needing notification from a follow-up clinic, OR 2.518 (1.179–5.376); and being beyond 15 months post-implantation, OR 5.440 (2.563–11.543). All cloud follow-up sessions were performed safely and efficiently, without any adverse events. 292 (89.8%) patients preferred cloud follow-up for future device management. Conclusion Compliance with routine in-office visits in this region has much room for improvement. Cloud follow-up addresses the limitations of an imbalanced distribution of follow-up clinics and geographic barriers for in-office CIED evaluation. Thus, cloud follow-up provides a potential solution to the current predicament of routine in-office visits in China.